OPTIMALISASI PERAN SOSIAL EKONOMI WAKAF DARI ASET WAKAF PADA YAYASAN MUSLIMIN KOTA PEKALONGAN - Jumailah Jumailah (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study will explain about the optimization of the socio-economic role of waqf from waqf assets, because so far people think that waqf is still functioned as a means of worship only. Law Number 41 of 2004 is the starting point for the management of waqf in Indonesia. That the law provides an understanding that the management and development of waqf assets can be carried out productively to improve the social and economic welfare of the community. This research is a field research which takes place at the Pekalongan City Muslimin Foundation (YMKP) with the type of qualitative research. This study states that the management of the waqf assets of the Pekalongan City Muslimin Foundation has economic benefits for the community, although not optimally. To optimize the role of waqf in the Pekalongan City Muslimin Foundation, it is necessary to optimize the role of Nazhir because Nazhir has a very strategic function in managing waqf assets so that coordination between Nazhir and the Indonesian Waqf Board (BWI) is necessary as a guidance function and the Office of Religious Affairs (KUA) as Officials. The maker of the Wakaf Pledge Deed (PPAIW) as a control function. So that waqf can function as an alternative to improve the social and economic welfare of the community